ASEAN Open Sky Agreement and The Challenges to Indonesia's Airspace Sovereignty: An Analysis of Legal Harmonization and Protection of National Interests - Vincent Raditya; Burham Pranawa; Ananda Megha Wiedhar Saputri; Sri Budi Raharjo (Greenation Research & Yayasan Global Resarch National, 2026)
The ASEAN Open Sky Agreement is a regional integration instrument aimed at liberalizing air transportation services between ASEAN member states. For Indonesia, the implementation of this agreement has legal and economic consequences, particularly regarding airspace sovereignty, the application of the Cabotage principle, and the protection of national interests. This study aims to analyze the implementation of the ASEAN Open Sky Agreement in Indonesia, its impact on the national economy, and its harmonization with the national legal system. The study employs a normative juridical method, drawing on legislative, conceptual, and international approaches. The legal materials used include the 1944 Chicago Convention, ASEAN agreements in the field of aviation, Law Number 1 of 2009 concerning Aviation, and other related regulations. The results show that the implementation of the ASEAN Open Sky Agreement does not eliminate state sovereignty over airspace, but rather constitutes a form of exercising sovereignty through a valid international agreement. The Cabotage principle remains an important legal instrument in protecting the national aviation industry from the pressures of regional market liberalization. On the other hand, this policy provides economic benefits through increased connectivity, tourism, trade, and investment. Therefore, this study offers a legal harmonization model as an integrative approach in balancing aviation liberalization with the protection of national interests.